Leader Behavior as a Determinant of Health at Work: Specification and Evidence of Five Key Pathways. (February 2014) - Wegge, Jürgen; Shemla, Meir; Haslam, S. Alexander
The extent to which leadership influences employee health and the processes that underlie its effects are not well understood at present. With the aim of filling this gap, we review four distinct forms of leader behavior (task-oriented, relationship-oriented, change-oriented, and passive/destructive) and clarify the different ways in which these can be expected to have a bearing on employee health. Next, we present a model that integrates and extends these insights. This model describes five pathways through which leader behavior can influence the health of organizational members and summarizes what we know about the most important determinants, processes (mediators) and moderators of these relationships. These involve leaders engaging in person-focused action, system- or team-focused action, action to moderate the impact of contextual factors, climate control and identity management, and modelling. Finally, we identify important gaps and opportunities in the literature that need to be addressed in future research. A key conclusion is that while much has been done to explore some key pathways between leadership and health, others remain underexplored. We also outline how future research might address these in the context of a more expansive theoretical, empirical and practical approach to this emerging field of research.